An integrated approach of MAS-CommonKADS, Model–View–Controller and web application optimization strategies for web-based expert system development - Hasan, S.S.; Isaac, R.K. (Expert systems with applications, 2011)
Web-based expert system development has been considered as complex, multidisciplinary and knowledge driven process. This paper presents a framework for development of web-based expert system with integrated approach of MAS-CommonKADS agent-oriented methodology, Model–View–Controller (MVC) architecture and web applications optimization strategies to deal with complexity of development and to achieve high usability. Study will guide in software engineering of developing such system with respect to Internet Technologies. Application of proposed framework for developing web-based expert system in sugarcane disorder diagnosis has been demonstrated. Results indicate that proposed methodology better deal with complexity of web-based expert system development and usability.